2021
DOI: 10.1093/g3journal/jkab439
|View full text |Cite
|
Sign up to set email alerts
|

A sensitized genetic screen to identify regulators of Caenorhabditis elegans germline stem cells

Abstract: GLP-1/Notch signaling and a downstream RNA regulatory network maintain germline stem cells (GSCs) in Caenorhabditis elegans. In mutants lacking the GLP-1 receptor, all GSCs enter the meiotic cell cycle precociously and differentiate into sperm. This dramatic GSC defect is called the “Glp” phenotype. The lst-1 and sygl-1 genes are direct targets of Notch transcriptional activation and functionally redundant. Whereas single lst-1 and sygl-1 mutants are fertile, lst-1 sygl-1 double mutants are sterile with a Glp … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Subunits of the DNA polymerase alpha–primase complex: Yoon et al found that DIV-1 (regulatory subunit) is indispensable for GLP-1/Notch-mediated germ cell proliferation during early larval development, whereas POLA-1 (catalytic subunit) and two primase subunits, PRI-1 and PRI-2, play a crucial role in GLP-1/Notch-mediated maintenance of proliferative cell fate during adulthood [ 17 ]. Robinson-Thiewes et al also identified POLE-1 (the catalytic subunit of DNA polymerase e) as a regulator of germ cell proliferation [ 18 ].…”
Section: Glp-1/notch-activation-mediated Tumorigenesis: Ectopic Proli...mentioning
confidence: 99%
“…Subunits of the DNA polymerase alpha–primase complex: Yoon et al found that DIV-1 (regulatory subunit) is indispensable for GLP-1/Notch-mediated germ cell proliferation during early larval development, whereas POLA-1 (catalytic subunit) and two primase subunits, PRI-1 and PRI-2, play a crucial role in GLP-1/Notch-mediated maintenance of proliferative cell fate during adulthood [ 17 ]. Robinson-Thiewes et al also identified POLE-1 (the catalytic subunit of DNA polymerase e) as a regulator of germ cell proliferation [ 18 ].…”
Section: Glp-1/notch-activation-mediated Tumorigenesis: Ectopic Proli...mentioning
confidence: 99%
“…Yoon et al found that DIV-1 (regulatory subunit) is indispensable for GLP-1/Notch-mediated germ cell proliferation during early larval development, whereas POLA-1 (catalytic subunit) and two primase subunits, PRI-1 and PRI-2, play a crucial role in GLP-1/Notch-mediated maintenance of proliferative cell fate during adulthood[16]. Robinson-Thiewes et al also identified POLE-1 (the catalytic subunit of DNA polymerase e) as a regulator of germ cell proliferation[17].…”
mentioning
confidence: 99%